2015
DOI: 10.7314/apjcp.2014.15.23.10427
|View full text |Cite
|
Sign up to set email alerts
|

Oral Potentially Malignant Disorders among Dental Patients: a Pilot Study in Jordan

Abstract: Background: To determine the prevalence, types, and risk factors of oral potentially malignant disorders (OPMDs) among a group of Arab Jordanian dental patients, and to evaluate their awareness and attitudes toward early diagnosis and treatment. Materials and Methods: A total of 1,041 patients attending a University Hospital for dental care were examined for the presence of OPMDs. Histopathological examination was performed on all cases clinically diagnosed and patients were directly interviewed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…Some oral cancers are preceded by noticeable mucosal changes known as OPMDs (Hassona et al, 2014;Scully, 2014). Leukoplakia and erythroplakia are the best known OPMDs, although other diseases such as oral lichenoid lesions, chronic hyperplastic candidiosis, and submucous fibrosis might also transform to cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some oral cancers are preceded by noticeable mucosal changes known as OPMDs (Hassona et al, 2014;Scully, 2014). Leukoplakia and erythroplakia are the best known OPMDs, although other diseases such as oral lichenoid lesions, chronic hyperplastic candidiosis, and submucous fibrosis might also transform to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Early-stage oral cancers are often asymptomatic and present clinically as a white or red patch, ulcer, or lump. Emphasis, therefore, has been placed on opportunistic screening of the oral mucosa by medical and dental practitioners as a proactive preventative measure which Y Hassona 1 *, F Sawair 1 , Z Baqain 1 , W Maayta 1 , A Shahin 1 , C Scully 2 may lead to reduced morbidity and mortality from oral cancer (Warnakulasuriya et al, 1991;Hassona et al, 2014;. In addition, patients with oral lesions are often first seen by general practitioners, both medical and dental.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is replete with studies about prevalence of oral mucosal lesions in different populations from both developed and developing countries . However, only a few studies specifically examined the relative frequency of pigmented oral lesions .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding age, the average OPMD presentation in our study was 55 years. The literature reports that these lesions occur mainly after 40 years 18 . For example leukoplakia, the average age found in our study was 55 years old, agreeing with previously reported data, which fluctuates between 40 and 60 years 14 .…”
Section: Discussionmentioning
confidence: 99%